PENGARUH PERSEPSI KEADILAN DALAM KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi Pada Karyawan PT.Telkom Indonesia Witel Jatim SelatanMalang) - Utari, Nyla Myrda; Azzuhri, Misbahuddin (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aimed to observe the influence of perception of equity in compensation which consists of the aspects are external equity, internal equity, individual equity, and procedural equity that influence employee job satisfaction in PT.  Telkom  Indonesia  Witel  Jatim  Selatan  Malang.  This  kind  of  research  is explanatory  research.  Data  were  obtain  using  a  questionnaire.  The  sample  in  this research is 64 peoples were determined by Slovin method. The result showed are: (1) Perception of equity in compensation is directly significant positive effect on job satisfaction, (2) external equity have a significant effect on job satisfaction, (3)internal equity haven’t a significant effect on job satisfaction, (4) individual equity have a significant effect on job satisfaction, (5) procedural equity have a significant effect on job satisfaction.   Keywords:   perception of equity in compensation, external equity, internal equity, individual equity, procedural equity, job satisfaction